Synchronous advanced gastric adenocarcinoma and advanced esophageal squamous cell carcinoma - Herbella, Fernando Augusto Mardiros; Lourenço, Laércio Gomes; Grande, José Carlos Del; Possik, Rafael; Haddad, Chibly Michel (São Paulo Medical Journal, 2002)
CONTEXT: Synchronous associations of esophageal and gastric cancers are not a common finding, especial ly with differing histological types and both tumors in advanced forms. A case with such an association is presented, in which an unusual therapy was proposed: palliative gastrectomy and esophageal intubation. CASE REPORT: A 75-year-old white man was referred to our service complaining of malaise and weight loss for one year and dysphagia and vomiting for 2 months. The patient had sought out medical consultation as a result of the latter two complaints.